miR-7-5p Affects Brain Edema After Intracerebral Hemorrhage and Its Possible Mechanism - Chen, Xiqian; Deng, Shuwen; Lei, Qiang; He, Qiang; Ren, Yijun; Zhang, Yiliu; Nie, Jingjing; Lu, Wei (Frontiers in Cell and Developmental Biology, 2020)
Objective: To explore the relationship between miR-7-5p and brain edema after intracerebral hemorrhageand the role of butylphthalide(NBP) in brain edema after intracerebral hemorrhage Method:Routinebloodtesting,,C-reactive protein results,and computed tomographydatawerecollected 1, 7 and 14 days after intracerebral hemorrhage in Six patients. Levels of MMP-9, ZO-1, occludin, IL-6, TNF-α, andmiR-7-5p were detectedin each patient’s serum. Sixty male Sprague-Dawley rats were randomly divided into sham operation, intracerebral hemorrhage and NBP treatment groups. Dry-wet weight was used to assess brain edema and Evans blue staining was used to assessthepermeabilityof the blood-brain barrier. Expression levels of IL-6, TNF-a, ZO-1 and occludin, PI3K, AKT, p-AKT, AQP4,andmiR-7-5p were analyzed in the rat brains. Result: The blood neutrophil-lymphocyte ratio (NLR) onday1 was associated with the area of brain edema onday7. The expression of miR-7-5p decreased after intracerebral hemorrhage, and as a result, the inhibition of the PI3K/AKT pathway was weakened.The decreased inhibition of the PI3K/AKT pathway resulted in an increase in AQP4expression,which further aggravated brain edema. NBP can upregulate the expression of miR-7-5p, affecting these pathways to reduce brain edema. Conclusion: After intracerebral hemorrhage, miR-7-5p expression in brain tissue is reduced, which may increase the expression of AQP4 by activating the PI3K/AKT pathway. NBP can inhibit thisprocess and reduce brain edema.